Discovery of the imidazole-derived GPR40 agonist AM-3189. Issue 1 (1st January 2016) - Ma, Zhihua; Lin, Daniel C.-H.; Sharma, Rajiv; Liu, Jinqian; Zhu, Liusheng; Li, An-Rong; Kohn, Todd; Wang, Yingcai; Liu, Jiwen (Jim); Bartberger, Michael D.; Medina, Julio C.; Zhuang, Run; et al.
Graphical abstract: As a follow-up to the GPR40 agonist AMG 837, which was evaluated in clinical trials for the treatment of type II diabetes, further optimization led to the discovery of AM-3189 (13k ). AM-3189 is representative of a new class of compounds with minimal CNS penetration, superior pharmacokinetic properties and comparable in vivo efficacy. Abstract: As a follow-up to the GPR40 agonist AMG 837, which was evaluated in clinical trials for the treatment of type II diabetes, further optimization led to the discovery of AM-3189 (13k ). AM-3189 is representative of a new class of compounds with minimal CNS penetration, superior pharmacokinetic properties and in vivo efficacy comparable to AMG 837.